Characterization of chitinases of Beauveria bassiana (Bv ) induced in semisolid-state fermentation - Lovera Sotelo, Yuli Andrea; Belaich, Mariano Nicolás; Mejía Pineda, Cindy Carolina; Villamizar Portilla, Laura Natalia; Patarroyo, Manuel A.; Barrera Cubillos, Gloria Patricia (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
A major consideration in the development of biopesticides based on entomopathogenic fungi has been the virulence and pathogenicity in terms of mean time of mortality and mean lethal concentration against the target insect. Virulence factors as chitinases degrade insect chitin facilitating the hyphal penetration through the cuticle. In this sense, Beauveria bassiana chitinases are an important cuticle-degrading group of enzymes implicated in the pathogenesis to insects, with high potential to develop biotechnological tools for in pest control. The aim of this study was to characterize chitinases produced by a Colombian strain of B. bassiana (Bv062) isolated from a Diatraea sp. larvae naturally infected in a sugar cane crop.